Intragenic enhancers act as alternative promoters. - Kowalczyk, MS; Hughes, J; Garrick, D; Lynch, MD; Sharpe, J; Sloane-Stanley, J; McGowan, S; De Gobbi, M; Hosseini, M; Vernimmen, D; Brown, J; Gray, N; et al. (Cell Press, 2012)
A substantial amount of organismal complexity is thought to be encoded by enhancers which specify the location, timing, and levels of gene expression. In mammals there are more enhancers than promoters which are distributed both between and within genes. Here we show that activated, intragenic enhancers frequently act as alternative tissue-specific promoters producing a class of abundant, spliced, multiexonic poly(A)(+) RNAs (meRNAs) which reflect the host gene's structure. meRNAs make a substantial and unanticipated contribution to the complexity of the transcriptome, appearing as alternative isoforms of the host gene. The low protein-coding potential of meRNAs suggests that many meRNAs may be byproducts of enhancer activation or underlie as-yet-unidentified RNA-encoded functions. Distinguishing between meRNAs and mRNAs will transform our interpretation of dynamic changes in transcription both at the level of individual genes and of the genome as a whole.